Peningkatan Kapasitas Produksi dan Manajemen Kelompok Tani Singkanaung melalui Pendampingan Teknologi Tepat Guna di Desa Mokoditek, Bolaang Mongondow Utara - Montolalu, Friska; Rumondor, Fadly; Potalangi, Nerni; Mege, Revolson; Soputan, Grace; Mokosuli, Yeremia; Pomalingo, Moh Fikri (Servitium Smart Journal, 2025)
Mokoditek Village in North Bolaang Mongondow has great agricultural potential, especially in corn and rice production. However, low productivity and limited technology have caused local farmer groups, especially the Singkanaung Farmers Group, to be unable to optimize their agricultural output. This research aims to increase the production capacity and management of farmer groups through the application of appropriate technology and intensive training. The results of the program showed an increase in corn productivity from 3 tons/ha to 4 tons/ha. In addition, financial management training has strengthened the capacity of farmer group members to manage agricultural businesses more efficiently and sustainably.